Distributed Global Debris Thickness Estimates Reveal Debris Significantly Impacts Glacier Mass Balance. Issue 8 (28th April 2021) - Rounce, D. R.; Hock, R.; McNabb, R. W.; Millan, R.; Sommer, C.; Braun, M. H.; Malz, P.; Maussion, F.; Mouginot, J.; Seehaus, T. C.; Shean, D. E.
Abstract: Supraglacial debris affects glacier mass balance as a thin layer enhances surface melting, while a thick layer reduces it. While many glaciers are debris‐covered, global glacier models do not account for debris because its thickness is unknown. We provide the first globally distributed debris thickness estimates using a novel approach combining sub‐debris melt and surface temperature inversion methods. Results are evaluated against observations from 22 glaciers. We find the median global debris thickness is ∼0.15 ± 0.06 m. In all regions, the net effect of accounting for debris is a reduction in sub‐debris melt, on average, by 37%, which can impact regional mass balance by up to 0.40 m water equivalent (w.e.) yr ‐1 . We also find recent observations of similar thinning rates over debris‐covered and clean ice glacier tongues is primarily due to differences in ice dynamics. Our results demonstrate the importance of accounting for debris in glacier modeling efforts. Plain Language Summary: Many glaciers around the world have a layer of debris (boulders, rocks, and sand) covering the underlying ice over much of the glacier surface, yet global glacier models do not account for debris because the debris thickness is unknown. Here we provide the first estimates of debris thickness for debris‐covered glaciers globally and show the debris substantially reduces regional glacier mass loss. We also find that recent observations that debris‐covered and clean ice glaciers are thinning at similar speeds is primarily due to differences in how glaciers flow. Our results fundamentally advance our ability to account for debris in glacier reconstructions, landscape evolution models, hazard assessments, and glacier projections of glacier runoff and their contribution to sea‐level rise. Key Points: We produce the first distributed global debris thickness estimates Accounting for debris significantly reduces regional glacier mass loss The similar thinning rates of debris‐covered and clean ice glaciers in High Mountain Asia is primarily caused by differences in ice dynamics